2005
DOI: 10.1103/physreva.71.032309
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-state transfer via the ferromagnetic chain in a spatially modulated field

Abstract: We show that a perfect quantum state transmission can be realized through a spin chain possessing a commensurate structure of energy spectrum, which is matched with the corresponding parity. As an exposition of the mirror inversion symmetry discovered by Albanese et. al (quant-ph/0405029), the parity matched the commensurability of energy spectra help us to present the novel pre-engineered spin systems for quantum information transmission. Based on the these theoretical analysis, we propose a protocol of near-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(210 citation statements)
references
References 12 publications
4
206
0
Order By: Relevance
“…Hahn [18,19,20], q-Krawtchouk [21] and q-Racah [10]. Of particular interest for what follows are models connected to the so-called para-Krawtchouk polynomials [13].…”
Section: A Review Of Perfect State Transfer In a XX Spin Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Hahn [18,19,20], q-Krawtchouk [21] and q-Racah [10]. Of particular interest for what follows are models connected to the so-called para-Krawtchouk polynomials [13].…”
Section: A Review Of Perfect State Transfer In a XX Spin Chainmentioning
confidence: 99%
“…Note that the Krawtchouk chain parameters are recovered when θ = 0 and that contrary to the isospectral models with fractional revival covered in the last section, here, all the J ℓ are modified in comparison with those of (3.19). Interestingly, the para-Krawtchouk models have been shown in [13] to enact PST for 18) where M 1 and M 2 are positive co-prime integers and M 1 is odd. Let us here explain how spin chains that lead to fractional revival can also exhibit perfect state transfer.…”
Section: The Bi-lattices Models and Para-krawtchouk Polynomialsmentioning
confidence: 99%
“…Choosing which lattice sites to place the spins on is a discretized form of the problem, and is not covered in this formalism. The best that we can achieve is to allow some additional engineering, such as local magnetic fields, and tune these to give the closest match to a particular spectrum [6]. We could envisage a variety of such systems in which we do not have control over a sufficient number of parameters.…”
Section: A Examplesmentioning
confidence: 99%
“…This wire would be a chain of qubits, with a fixed interaction, capable of transferring a quantum state from one end of the chain to the other. Following the initial investigation of wires [1], and subsequent demonstration that perfect quantum wires exist [2,3], a large number of papers have been published about optimising the schemes over a variety of parameters such as the robustness against errors, or a restricted ability to engineer the state (see, for example, [4,5,6,7]). Novel modifications of such chains have also been presented for the generation of entangled states or the application of unitary operations during the transfer [8].…”
Section: Introductionmentioning
confidence: 99%
“…This idea was first introduced in [1], where it was shown that the natural dynamics of a Heisenberg ferromagnetic spin chain can achieve high-fidelity transfer of qubits over distances as long as 80 lattice units.In contrast to this traditional "passive" protocol, different approaches soon emerged. One idea was to engineer the couplings between the various spins in the chain in such a way that states are transferred with perfect [2]- [9] or with arbitrary high fidelity [10]- [16]; in addition, some minimal external control on the chain dynamics was also introduced in order to achieve similar results [18]- [26].…”
Section: Introductionmentioning
confidence: 99%